Minimized Hemodiafiltration for Extracorporeal Membrane Oxygenation in Infants - Kwapil, Nicola; Teske, Andreas; Dittrich, Sven; Blumauer, Robert; Cuomo, Michela; Purbojo, Ariawan; Münch, Frank (Thoracic and Cardiovascular Surgeon, 2023)
BACKGROUND: Fluid overload is a serious complication in the treatment of infants with extracorporeal membrane oxygenation (ECMO). Volume overload leads to prolonged ECMO therapy if left untreated. The renal replacement therapy of choice in pediatric patients is peritoneal dialysis or conventional dialysis using a "large" hemofiltration machine via a Shaldon catheter or directly connected to the ECMO system. This study describes the implementation of a novel minimized hemodiafiltration (HDF) system in pediatric patients on ECMO. METHODS: This retrospective analysis included 13 infants up to 5 kg who underwent 15 veno-arterial (V-A) ECMO runs with HDF. A minimized HDF system is integrated into an existing ECMO system (18-mL priming volume), connected post-oxygenation to the venous line, before the ECMO pump. Two infusion pumps are attached to the inlet and outlet of the hemofilter to control the HDF system.In addition to retention values (creatine and urea) at six defined time points, flow rates, dialysis parameters, and volume withdrawal were examined, as well as the number of HDF system changes. RESULTS: With a mean ECMO runtime of 156 hours, the HDF system was utilized for 131 hours. The mean blood flow through the hemofilter was 192 mL/min. The mean dialysate flow was 170 mL/h, with a mean volume deprivation of 39 mL/h. The HDF system was changed once in seven cases and twice in three cases. CONCLUSION: There were no complications with the minimized HDF system in all 15 applications. It allows safe patient volume management when treating infants with ECMO, with effective elimination of urinary substances.
CRIS-Team Scopus Importer:2023-04-21